2010
DOI: 10.3109/00207454.2010.494790
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Patterns in Parkinson's Disease Patients with Visual Hallucinations

Abstract: Visual hallucinations (VHs) in Parkinson's disease (PD) can be a frequent and disturbing complication of the disease with 33% of PD patients undergoing long-term treatment experiencing VHs during the course of their illness. One line of evidence that is emerging as a possible risk factor in the occurrence of VHs is the sleep-wake cycle and sleep behavior in patients with PD. This study compared sleep patterns in a group of visually hallucinating Parkinson's patients with a group of nonhallucinating PD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…Several studies have suggested that cognitive dysfunction, hallucinations and sleep are related phenomena in PD (39,40). Our previous study (41) showed that patients with visual hallucinations had relatively worse sleep quality, which is consistent with previous studies showing that PD patients with hallucinations had reduced sleep efficiency and increased awakenings compared to PD patients without hallucinations (42). That study also showed that better cognition, especially in domains such as attention and orientation, may protect against hallucinations (41).…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have suggested that cognitive dysfunction, hallucinations and sleep are related phenomena in PD (39,40). Our previous study (41) showed that patients with visual hallucinations had relatively worse sleep quality, which is consistent with previous studies showing that PD patients with hallucinations had reduced sleep efficiency and increased awakenings compared to PD patients without hallucinations (42). That study also showed that better cognition, especially in domains such as attention and orientation, may protect against hallucinations (41).…”
Section: Discussionsupporting
confidence: 87%
“…--Psychosis[155,156] (psychosis more common in PD patients with EDS, and PD patients with hallucinations more likely to have unexpected EDS) [157]…”
Section: Figmentioning
confidence: 99%
“…Previous studies identified various risk factors for developing hallucinations in PD, such as older age, older age at onset, longer disease duration, depression, sleep disturbances (insomnia, REM‐sleep behavioral disorder [RBD], and excessive daytime sleepiness), cognitive impairment, severity of motor symptoms, and comorbidity . Hallucinations have also long been considered a side effect of long‐term levodopa treatment 2 ; more recent studies, however, have questioned this assumption, as a relation with levodopa dosage level has not been consistently found …”
mentioning
confidence: 99%